2016
DOI: 10.1186/s12915-016-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of whitefly Bemisia tabaci MEAM1, a global crop pest, provides novel insights into virus transmission, host adaptation, and insecticide resistance

Abstract: BackgroundThe whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is among the 100 worst invasive species in the world. As one of the most important crop pests and virus vectors, B. tabaci causes substantial crop losses and poses a serious threat to global food security.ResultsWe report the 615-Mb high-quality genome sequence of B. tabaci Middle East-Asia Minor 1 (MEAM1), the first genome sequence in the Aleyrodidae family, which contains 15,664 protein-coding genes. The B. tabaci genome is highly divergent from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
421
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(439 citation statements)
references
References 96 publications
16
421
0
2
Order By: Relevance
“…The release of the recently completely sequenced genome of B. tabaci MEAM1 makes it possible to identify stress‐responsive related gene families through comparative genomics approaches (Chen et al ., ). In this study, we found 26 Hsp genes encoding four types of insect Hsp s in the B. tabaci genome by comprehensive bioinformatic methods.…”
Section: Discussionmentioning
confidence: 97%
“…The release of the recently completely sequenced genome of B. tabaci MEAM1 makes it possible to identify stress‐responsive related gene families through comparative genomics approaches (Chen et al ., ). In this study, we found 26 Hsp genes encoding four types of insect Hsp s in the B. tabaci genome by comprehensive bioinformatic methods.…”
Section: Discussionmentioning
confidence: 97%
“…The Illumina reads of these libraries were submitted to the European Nucleotide Archive under the primary accession number PRJEB11628 and secondary accession numbers ERP013025 and SAMEA3643263‐SAMEA3643274; they were also deposited in the Sequence Read Archive database under accession number SRP064690. The genomic information of GST was from the published B.tabaci genomes (Chen et al ., ; Xie et al ., ). The candidate BtGST transcripts were confirmed by searching the BLASTX algorithm against the nonredundant NCBI nucleotide database using a cut‐off E‐value of 10 −5 .…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive understanding of OBPs and CSPs in B. tabaci requires a more complete genome‐wide analysis. In this research, we used previously published data on B. tabaci genomes (Chen et al ., ; Xie et al ., ) and new antenna transcriptome data (obtained in the current study) to complete a genome‐wide analysis of OBP and CSP gene families in B. tabaci MEAM1. We systematically classified, characterized, and phylogenetically analyzed the OBP and CSP genes.…”
Section: Introductionmentioning
confidence: 97%